In-Situ and Ex-Situ Conservation of Solanum xanthocarpum in Jaffna District - Vijayakumar, T.; Viviyan, S. (University of Jaffna, 2015)
Solanum xanthocarpum is important medicinal plant in traditional practices. It is known by the Tamil name “Kandankathari”. It means cutting phlegm from throat. It is used to treat the respiratory disorder in Indigenous medicine. The period of King Pararasasekaram and Sekarasasekaram, S. xanthocarpum cultivated and used in Jaffna. The books originated from Jaffna such as Pararasasekaram and Sekarasasekaram are clearly mentioned the plant of S. xanthocarpum in Slogams. At present S. xanthocarpum is imported from abroad. It is evident that Solanum xanthocarpum imported 2, 08650 Kg in 2011 from India. The land and climatic conditions are suitable to cultivate in Jaffna. The study objected to protect the naturally growing plant and cultivate to fulfill the required quantity of S. xanthocarpum. Study of In-situ conservation, the researcher made field visits to 15 DS areas to observe the naturally growing plant in 2013according to the field visits’ records of Gunapadam branch unit of Siddha medicine .The plants are available around the Vallipuram temple, Kudathanai, Nakarkovil in Pointpedro North and Vadamaradchi East DS division. More or less amount of plants noted in Velanai, Kayts and delft DS areas. Fewer amounts of plants noted in Thenmaradchi and Vadamaradchi North West DS areas. Rare in other DS areas but occasionally noted small group of plants. Study of Ex-situ conservation, Ten Larchum of land selected for the cultivation with the permission of DS. Genuine seeds were obtained from taxonomist. Four mother plants were selected to cultivate. 150 – 250 fruits collected from each plant. Nursery beds made to grow seedlings. 27 days later 1000 seedlings transferred to standard plots. 900 plants uprooted after 6 month. Among those 300 were small and 600 were large. This was nearly 825Kg cultivated. The study shows that the collection and cultivation practice in Jaffna district is succeeded. The researcher suggested that the proper collection and cultivation practice of Solanum xanthocarpum will be the benefit to the shareholders and country.
Keywords: Conservation; Ex-situ; In-situ; Kandankathari; Solanum xanthocarpum